Atypical Prolonged Viral Shedding With Intra-Host SARS-CoV-2 Evolution in a Mildly Affected Symptomatic Patient - Cunha, Marielton dos Passos; Vilela, Ana Paula Pessoa; Molina, Camila Vieira; Acuña, Stephanie Maia; Muxel, Sandra Marcia; Barroso, Vinícius de Morais; Baroni, Sabrina; Gomes de Oliveira, Lilian; Angelo, Yan de Souza; Peron, Jean Pierre Schatzmann; Góes, Luiz Gustavo Bentim; Campos, Angélica Cristine de Almeida; et al. (Frontiers in Medicine, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is caused by a respiratory virus with a wide range of manifestations, varying from asymptomatic to fatal cases, with a generally short outcome. However, some individuals present long-term viral shedding. We monitored 38 individuals who were mildly affected by the SARS-CoV-2 infection. Out of the total studied population, three (7.9%) showed atypical events regarding the duration of positivity for viral RNA detection. In one of these atypical cases, a previously HIV-positive male patient presented a SARS-CoV-2 RNA shedding and subgenomic RNA (sgRNA) detected from the upper respiratory tract, respectively, for 232 and 224 days after the onset of the symptoms. The SARS-CoV-2 B.1.1.28 lineage, one of the most prevalent in Brazil in 2020, was identified in this patient in three serial samples. Interestingly, the genomic analyses performed throughout the infectious process showed an increase in the genetic diversity of the B.1.1.28 lineage within the host itself, with viral clearance occurring naturally, without any intervention measures to control the infection. Contrasting widely spread current knowledge, our results indicate that potentially infectious SARS-CoV-2 virus might be shed by much longer periods by some infected patients. This data call attention to better adapted non-pharmacological measures and clinical discharge of patients aiming at preventing the spread of SARS-CoV-2 to the population.